1998
DOI: 10.1037/0021-9010.83.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Origins of coordination and team effectiveness: A perspective from game theory and nonlinear dynamics.

Abstract: Coordination occurs when 2 or more people do the same or complementary tasks at the same time; it takes several forms. The form of coordination studied here was similar to behavior at a 4-way stop traffic intersection. The performance task involved 12 4-person groups and a special card game. Split-plot analysis of variance (ANOVA) showed that coordination rules were implicitly learned and then transferred successfully to new rules of similar difficulty and that coordination can occur without verbal mediation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…Assessments consistent with the conceptualization sketched above have focused on temporal response patterns and sequential analysis (Zalesny et al, 1995), such as using observer ratings of communication patterns (Brannick, Roach, & Salas, 1993), measuring the amount of time one team member waits for another before engaging in a joint effort (Coovert, Campbell, Cannon-Bowers, & Salas, 1995), and using Petri Empirical research has established team coordination as an important correlate of team performance. For example, Guastello and Guastello (1998) reported that coordination rules were implicitly learned and then transferred successfully to new rules of similar difficulty. They also noted that team coordination may occur without verbal mediation or leadership actions and that coordination transfer was less positive to a task of greater difficulty.…”
Section: See March 2001 Issue Of Journal Of Organizational Behaviormentioning
confidence: 99%
“…Assessments consistent with the conceptualization sketched above have focused on temporal response patterns and sequential analysis (Zalesny et al, 1995), such as using observer ratings of communication patterns (Brannick, Roach, & Salas, 1993), measuring the amount of time one team member waits for another before engaging in a joint effort (Coovert, Campbell, Cannon-Bowers, & Salas, 1995), and using Petri Empirical research has established team coordination as an important correlate of team performance. For example, Guastello and Guastello (1998) reported that coordination rules were implicitly learned and then transferred successfully to new rules of similar difficulty. They also noted that team coordination may occur without verbal mediation or leadership actions and that coordination transfer was less positive to a task of greater difficulty.…”
Section: See March 2001 Issue Of Journal Of Organizational Behaviormentioning
confidence: 99%
“…The results of Intersection game experiments to date show that if the experimental task is not excessively difficult, the group will display a coordination learning curve (Guastello and Guastello, 1998). The coordination acquired during one task session will transfer to the learning and performance curve of a second task.…”
Section: Work Group Coordinationmentioning
confidence: 99%
“…NDS has extended this principle to the explanation of work group coordination, making it a group learning phenomenon (Guastello and Guastello, 1998;Guastello et aI., 2005a). Team members implicitly learn to coordinate with each other and entrain their behaviors to each other while engaging in a more explicit task learning objective.…”
Section: Learningmentioning
confidence: 99%
“…Where z is behavior and a is the Lyapunov exponent which is constrained to negative values (Guastello, 1995;Guastello and Guastello, 1998 …”
Section: Psyehophysiesmentioning
confidence: 99%
“…If the self-organization process is complete, as in the case of a feasible task, the common learning curve would result, which would in turn be characterized as a fixed point attractor, as in Eq. (4):Where z is behavior and a is the Lyapunov exponent which is constrained to negative values (Guastello, 1995;Guastello and Guastello, 1998 In the in event that learning is incomplete, an asymptote does not form, and the exponent in Eq. (4) or (5) is positive.…”
mentioning
confidence: 99%